013 Cases for Action: a new approach to addressing gaps between research evidence and health policy and practice in Australia. (15th August 2013) - Berry, M; McCallum, J; Ghersi, D; Fitzgerald, A; Clydesdale, J; Goodwin, A; Singh, A
Abstract : Background: In 2012, Australia's peak body for supporting health and medical research established a Research Translation Faculty of 2, 500 researchers to address challenges of translating research evidence into policy/practice. The initial focus of the Faculty is developing Cases for Action to address Australia's major health issues through high-level advocacy. Objectives: To work collaboratively with senior researchers to develop compelling cases for actions that could be taken to address the most significant gaps between research evidence and health policy/practice in Australia. Methods: Faculty members will search literature, consult with stakeholder networks and debate issues in developing a paper of published evidence, recommending actions to address each prioritised gap and providing the rationale for prioritisation. Steering Groups will oversee the development of each Case for Action. Results: This presentation will share the experiences and lessons learnt to-date in developing Cases for Action. Discussion: There is a gap between what we know and what we do. Cases for Action will draw on the combined expertise of researchers to systematically consider and prioritise actions to best address these gaps. Possible actions that could be proposed include advice to government about health policy, clinical or public health guidelines, or opportunities to collaborate with strategic partners to leverage investment in health or to provide support in the implementation of heath strategies. Implications for Guideline Developers/Users: The lessons learnt from the Cases for Action process will benefit attendees who are considering how to focus their effort to ensure that healthcare policy and practice best reflects available evidence.